Estimation and compensation for transmitter and receiver I/Q imbalance of full-duplex terminals - Hao-wei WU; Jun-bo ZHAO; Hao-ran XU; Jing-lan OU (Tongxin xuebao)
In order to reduce I/Q imbalance of the full-duplex terminal with direct-conversion transceiver,an algorithm based on self-interference signal was proposed for the estimation and compensation of I/Q imbalance in both transmitter (Tx) and receiver (Rx).Without the perfect transmitter or receiver for I/Q imbalance estimation,the self-interference signal from Tx chain to Rx chain was used for parameter estimation and separation,and the Tx and Rx I/Q imbalance parameters were obtained,respectively.Then the pre-compensation before transmission and the correction after receiving was processed,so that there was nearly no I/Q imbalance in this full-duplex terminal from the view of the other terminals,and the complexity of the signal processing will be reduced as a result of the absent of the I/Q imbalance estimation.The simulation results show that the proposed algorithm can effectively estimate and compensate the I/Q imbalance of the full-duplex Tx ＆ Rx terminal,and improve the overall signal quality and the system performance.